2007
DOI: 10.1002/asna.200710794
|View full text |Cite
|
Sign up to set email alerts
|

Coronal “wave”: A signature of the mechanism making CMEs largescale in the low corona?

Abstract: We analyse one of the first coronal waves observed by STEREO/EUVI associated with a source region just behind the limb, NOAA 10940. We apply the coronal "wave" model proposed by Attrill et al. (2007) to explain the evolution of the observed bright fronts, thereby arguing that the bright fronts and dimmings are due to magnetic reconnections between the expanding CME core and surrounding magnetic structures. We offer a discussion showing that this model provides a mechanism via which CMEs, expanding from a small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 27 publications
(34 reference statements)
0
49
1
Order By: Relevance
“…The observation of the CH crossing (or transmission) is a very strong argument for the wave nature of these EUV disturbances. Until now, it has been reported based on empirical evidence that coronal waves do not traverse CHs (e.g., Thompson et al 1999;Veronig et al 2006;Attrill et al 2007b;Ma et al 2009). However, transmission has been discussed in the simulations of Schmidt & Ofman (2010), who also discuss it in terms of waves launched by the "resonating" of the CH.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation of the CH crossing (or transmission) is a very strong argument for the wave nature of these EUV disturbances. Until now, it has been reported based on empirical evidence that coronal waves do not traverse CHs (e.g., Thompson et al 1999;Veronig et al 2006;Attrill et al 2007b;Ma et al 2009). However, transmission has been discussed in the simulations of Schmidt & Ofman (2010), who also discuss it in terms of waves launched by the "resonating" of the CH.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The pseudo-wave interpretation proposes several mechanisms all associated with the large-scale structure of the associated CME. One such pseudo-wave is the propagating reconnection front (Attrill et al 2007a(Attrill et al , 2007bvan Driel-Gesztelyi et al 2008), in which, as the CME is expanding, it interacts with the smaller scale loops in the vicinity via reconnection to produce heat and enhanced EUV intensity. Another possible pseudo-wave mechanism is the disk projection of large-scale current shells that surround the expanding flux-rope core of a CME (Delannée et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Observations of EUV waves revealed a series of features which strongly appeal to pseudo-wave interpretations (Attrill et al, 2007a(Attrill et al, ,b, 2009Cohen et al, 2009;Zhukov, Rodriguez, and de Patoul, 2009;Dai et al, 2010;Schrijver et al, 2011;Warmuth and Mann, 2011). These include stationary brightenings, large-scale secondary dimmings and erratic (including a series of accelerations and decelerations) or "slow" (i.e.…”
Section: Brightenings Secondary Dimmings and Volume Expansionsmentioning
confidence: 97%
“…The latter is the key weakness of this interpretation, as (2000)). Pseudo-wave -current shell (panel (b), from Delannée et al (2008)), pseudo-wave -reconnection front, (panel (c), from Attrill et al (2007a)) ; hybrid pseudo-wave + MHD wave/shock,(panel (d), from Chen et al (2002)). Panels (a), (c) and (d) reproduced by permission of the AAS.…”
Section: Introductionmentioning
confidence: 99%
“…By analysing TRACE data Ballai et al (2005) showed that EIT waves observed by the EUV instrument exhibit oscillatory behaviour with a period of approximately 400 seconds. In contrast, Attrill et al (2007) illustrated a model where EIT waves are, in fact, a succession of reconnection events.…”
Section: Introductionmentioning
confidence: 99%